Left Posteroventral Pallidotomy Results in a Deficit in Verbal Memory - S. F. Crowe; J. D. O’Sullivan; R. F. Peppard; P. M. McNeil; F. Bardenhagen; S. Bowden (Behavioural Neurology, 1998)
Whilst pallidotomy is emerging as a popular approach to the treatment to Parkinson’s disease, little is yet known about the cognitive effects of this procedure. This study presents 19 patients (6 right, 13 left) who were assessed both before and after the procedure on a battery of cognitive tests. The results indicate that subjects with left-sided lesions display significant decline in verbal memory between one and three months following the procedure. The results are consistent with the notion of either a classic amnesic syndrome or a deficit in striato-frontal working memory.